High temperature tensile properties of centrifugally cast in-situ Al-Mg2Si functionally graded composites for automotive cylinder block liners - Ram S.C.; Chattopadhyay K.; Chakrabarty I. (My University, 2025)
The effect of Mg content (2.5 and 7.5 wt%) on the development of centrifugally cast in-situ A356-Mg2Si composite functionally graded material (FGM) has been investigated. The secondary dendrite arm spacing (SDAS) has the effect on size and volume% of Mg2Si particles. FGMs are characterized by optical and scanning electron microscopy, X-ray diffraction analysis, measurement of hardness and room and elevated temperature tensile properties (UTS). The microstructural features are correlated with room temperature and high temperature tensile properties at 150 °C and 300 °C. Since the population of Mg2Si particles are maximum at inner zones, the tensile strengths at these zones are maximum among the three zones. The room temperature tensile strength of FGM with 7.5 wt% Mg shows maximum value however it decreases at higher temperatures. The peak UTS of both FG composites in all three zones are attained at around 150 °C. Maximum peak UTS of 178 MPa is obtained with A356–2.5%Mg at this temperature. As the test temperature is increased, the fracture mode is changed from mixed mode to ductile mode. Particle cracking and decohesion of particles from the softer matrix are responsible for these two modes respectively. © 2017 Elsevier B.V.